Media Film untuk Pembelajaran Maharah Istima’ di Pondok Pesantren Modern Gontor Putri: Implementasi dan Analisis Respon Santriwati - Bela Noviana Dewi (IAIN Madura, 2022)
Teaching Arabic is a formidable challenge for some teachers. Not infrequently they encounter difficulties and obstacles when explaining a material to students. Therefore, teachers are required to be able to choose the right learning media so that students do not get bored and have a great interest in learning Arabic. Technological advances provide fresh air for teachers, because there are many modern media that can be used, one of which is using films. This study aims to explain the process of using film as a learning medium for listening skill of santriwati at Pondok Modern Darussalam Gontor Putri 1 and their responses during the learning process. The researcher uses a qualitative descriptive method with a field study approach. Data were collected using observation, interviews and documentation studies and then analyzed by means of observation during the learning activities using films. The result of this research is that film can be used as an interesting medium for learning the Arabic language maharah istima' and makes students more enthusiastic with a combination of audio and visual.